Patient satisfaction with nurse-delivery primary health care services in Free State and Gauteng provinces, South Africa: A comparative study - Wilfred N. Nunu; Pascalia O. Munyewende (AOSIS, 2017)
Background: The majority of health care users in South Africa utilise primary health care (PHC) services where these services are free at the point of entry. There is a dearth of knowledge on the factors influencing patient satisfaction with PHC clinic services. Aim: This study compared patient satisfaction with PHC services in the Free State (FS) and Gauteng (GP) provinces Setting: Secondary data analysis was conducted on a cross-sectional survey obtained from the Research on the State of Nursing Project run by the Centre for Health Policy in 2012. Methods: A pre-tested satisfaction survey questionnaire with questions on facility evaluation, experience with providers and receipt of medication was administered to 1110 systematically randomly sampled adult patients attending antiretroviral, hypertension, diabetes and tuberculosis services. Results: Of 1110 respondents, 1096 responded to the patient satisfaction survey signifying a 98.8% response rate. Over 60% of respondents were women in both provinces. Over 90% of patients were satisfied with PHC services in both provinces. Factors associated with satisfaction in GP and FS were time spent waiting for consultation, nurses listened, being given information on condition and being treated politely. Having privacy respected came out as a significant factor in FS. Conclusions: High levels of satisfaction with PHC services were experienced by study participants in both provinces. Satisfied patients adhere to treatment plans and have better health-seeking behaviour, which translates to improved clinical outcomes. Therefore, nurses should continue listening, respecting and treating their patients with politeness, and also implement efficient work schedules to reduce patient waiting times.